Analysis of high school students' critical thinking ability in environmental change material through POE learning - Adika Muhammad Aziz; Diana Rochintaniawati; Mimin Nurjhani Kusumastuti; Eni Nuraeni (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2025)
Critical thinking skills are important to master in facing global competition. Biology learning in class must be oriented to improving critical thinking skills. Environmental change material is biology material that requires students to think critically in responding to environmental problems. One way to improve critical thinking skills is to use POE learning strategies that able to train students to be critical of problem. This research aims to provide an overview of students' critical thinking abilities on environmental change material which is improved through the POE learning strategy. This research uses a qualitative descriptive method with the data used in analyzing the data from observations, teacher teaching modules, student responses, student worksheet answers, and interviews. The results of this research provide an overview of several shortcomings in implementing POE learning strategies in environmental change material so that students' critical thinking abilities are still low. These shortcomings include the observation stage which was not carried out optimally, the student worksheet stage did not train critical thinking skills, the environmental problem topic was too big, the learning allocation was not good, and the teacher's involvement in guiding students was still lacking. With this research, a picture of the implementation of POE learning strategies in biology learning can be seen clearly so it is hoped that it can become good initial research for future research.Abstrak. Kemampuan berpikir kritis penting untuk dikuasai dalam menghadapi persaingan global. Pembelajaran biologi di kelas harus berorientasi untuk meningkatkan kemampuan berpikir kritis. Materi perubahan lingkungan merupakan materi biologi yang menuntut siswa untuk berpikir kriris dalam menanggapi permasalahan lingkungan. Salah satu cara meningkatkan kemampuan berpikir kritis adalah dengan menggunakan strategi pembelajaran POE yang mampu melatihkan siswa kritis terhadap objek permasalahan. Tujuan dari penelitian ini adalah untuk memberikan gambaran kemampuan berpikir kritis siswa pada materi perubahan lingkungan yang ditingkatkan melalui strategi pembelajaran POE. Penelitian ini menggunakan metode deskriptif kualitatif dengan data yang digunakan dalam menganalisis adalah data hasil observasi, modul ajar guru, respon siswa, jawaban lembar kerja siswa, dan wawancara. Hasil penelitian ini memberikan gambaran tentang beberapa kekurangan dalam pelaksanaan strategi pembelajaran POE pada materi prubahan lingkungan sehingga kemampuan berpikir kritis siswa masih rendah. Kekurangan tersebut diantaranya adalah tahapan observe yang dilakukan tidak secara optimal dilakukan, tahapan lembar kerja siswa yang tidak melatihkan kemampuan berpikir kritis, topik permasalahan lingkungan yang terlalu besar, alokasi pembelajaran yang kurang baik, dan keterlibatan guru dalam membimbing siswa masih kurang. Dengan adanya penelitian ini, gambaran pelaksanaan strategi pembelajaran POE dalam pembelajaran biologi dapat terlihat jelas sehingga diharapkan mampu menjadi penelitian awal yang baik bagi penelitian-penelitian yang akan datang.